Education, Human Capital, and Growth: A Personal Perspective - Griliches, Zvi (Journal of Labor Economics, 1997)
This article reviews the literature on the relationship of economic growth to the education levels of the labor force. The emphasis is on Yoram Ben-Porath's contribution to some of the issues in this field: the endogeneity of schooling, the role of the public sector as an "absorber" of educated labor, and the importance of personal human capital created by investments in reputation and personal relationships, the F-connection